(3JbfjGJ hfXe eYGUQI aj EOGQI GdYedjGJs - (3ZSGf bGSe(B, (3GddGejs ((3YeGf(B:s (3EKQGA ddfTQ hGdJhRjY(B,s, 2008)
(3GdJbfjGJ GdeSJNOeI dEOGA hXjaI GdYedjGJ(B- (3JbfjGJ JWhjQ GdefJL(B- (3JbfjGJ JQJjH GdeUfY(B- (3JbGfI GdeYdheGJ aj eLGdGJ GdEfJGL(B- (3fXGe JNWjW GdEMJjGLGJ GdeGOjI(B- (3fXGe GdEjUGA GdhGSY(B- (3fXGe GdJUfjY GdaYGds
(3GdeQGLY U(B.313(3; CSFdI ddeQGLYI U(B.311s
Keywords: (3EOGQI GdEfJGLs; (3EOGQI GdYedjGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s